2018
DOI: 10.1111/jocn.14343
|View full text |Cite
|
Sign up to set email alerts
|

Marital relationship and health‐related quality of life of patients with prostate cancer and their spouses: A longitudinal clinical study

Abstract: These findings may be useful when counselling of patients with prostate cancer and their spouses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…This may cause bias since unsatisfactory marriage can result in immune dysregulation [30]. Previous study revealed that marital relationship may change after cancer diagnosis [31]. The SEER database did not provide information on change of marital status after G-NEN diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause bias since unsatisfactory marriage can result in immune dysregulation [30]. Previous study revealed that marital relationship may change after cancer diagnosis [31]. The SEER database did not provide information on change of marital status after G-NEN diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined specific relationship-enhancing and compromising communication behaviours using longitudinal data. Prior longitudinal studies evaluating relationship factors have assessed general relationship satisfaction (Chien et al, 2018;Harju et al, 2018;Ross et al, 2016) or general open communication (Song et al, 2011(Song et al, , 2016 This study had two aims. The first aim was to characterise changes in couples' depressive symptoms, general psychological adjustment, cancer-specific distress and cancer-related concerns over a 6 month period.…”
mentioning
confidence: 99%
“…In Finland, relatively little research has investigated the experiences and support needs of cancer patients' close ones. Studies have focused on the experiences of mental health professionals who use structured family-centred interventions to support the children of cancer patients (Niemelä et al, 2010), quality of life of patients with breast cancer (Salonen, 2011), perceptions of electronic social support (Yli-Uotila, 2017) and marital relations and health-related quality of life questions in patients with prostate cancer and their spouses (Harju et al, 2018). Lehto-Järnstedt et al (2004), Lehto et al (2015Lehto et al ( , 2018 have performed research, for example, on cancer patients' social support.…”
Section: Previous Studiesmentioning
confidence: 99%